Pengaruh Likuiditas, Leverage, dan Profitabilitas terhadap Nilai Perusahaan pada Perusahaan Industri Sektor Coal Production yang Terdaftar di BEI Tahun 2020-2023 - Kusuma, Vidia Nanda; Mahroji, Mahroji (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
Companies are founded to obtain maximum or maximum profits and to achieve their goals in the form of company value. In this way, a company can develop continuously and provide returns that benefit the company owner so that the company can prosper. This research aims to see the effect of liquidity (CR), leverage (DER), profitability (ROA) on company value in industrial companies in the coal production sector listed on the IDX in 2020-2023 in the company's financial reports. In this research, there are 26 companies that have been selected using purposive sampling criteria with samples from mining industry companies in the coal production sub-sector listed on the IDX consecutively for 4 years in 2020-2023, companies that use the rupiah as their currency in reporting. Financial year 2020 – 2023, companies that have complete financial reports consecutively from 2020-2023. So the sample obtained was 26 companies with 104 data studied. The data used is secondary data in the form of financial reports obtained from the site www.idx.co.id. The research design uses the causality method. The data analysis technique used is multiple regression. The results of this research show that liquidity has a significant positive effect on company value. Leverage has a significant positive effect on company value. Profitability has a significant positive effect on company value. Future researchers will be able to add additional variables in the hope of making comprehensive findings that are also relevant to various situations for various business industries so that the coefficient values ​​are normal or not too low. The value of the company will be an important consideration for investors when investing in the company, because the value of the company lies in the activity of evaluating the development of the company itself.